Cyberfeminist collectives as information source - Woida, Luana Maia [UNESP] (Universidade Federal de Santa Catarina (UFSC), 2020)
Objective: To analyze cyberfeminist collectives as a source of information, whose problems include questioning whether these websites provide bibliography suggestions with publications that address the theme, identify what are the types of materials (ebooks, articles, videos, dissertations, theses, booklets, laws, etc.) made available, who accesses them, who produces them, and if the access of materials are measured. Methods: We opted for an exploratory research using the virtual ethnography method, evaluating the Brazilian feminist groups highlighted in the researched literature: Think Olga, Não Me Kahlo, Geledés, Blogueiras Negras, Escreva Lola Escreva, Blogueiras Feministas, Biscate Social Club, Gorda and Sapatão, Transfeminismos. Results: Most of the collectives studied present textual postings, many of which are built on the writer’s awareness and knowledge of the subject, some follow an approach similar to a statement, showing a personal perception of the subject, while others present a more neutral discussion. Searching for information on these blogs and websites, as well as social media pages, is not always easy, since some of them have tags and search boxes, but not all of them. They position themselves as to the possible audience, however it was not found how many accesses are made. Readers’ comments are an indicator that there is in the materials provided, but there is not a map of accesses of who and how much was accessed. Conclusions: It is considered that Information Science is substantial for cyberfeminism, as it contributes directly to women’s empowerment, since it aims to understand the dynamics of development and diffusion of an information culture in this environment, and one of the main proposals is to promote access and women’s ownership of information.
Coletivos Ciberfeministas Como Fonte De Informação
Keywords: Cyberfeminism; Feminist collectives; Feminist movement; Source of information